Plants of Haryana useful in dermatological disorders: An Ethnobotanical Survey - Yadav, Sanjay; Arya, Vedpriya; Kumar, Sandeep; Yadav, J. P. (Pharmacognosy Reviews)
Haryana is a state of northern India has a great history and diversity of medicinal plants. The importance of medicinal plants in traditional healthcare practices provides clues to new areas of research. In the present study, we have enlisted the traditional medicinal plants knowledge of people of rural communities of Haryana in curing several skin diseases. The information was collected by questionnaires and interviews of old experienced people and local healers of villages. Local people are using the crude formulations to cure their skin problems. It was found that 35 different plant species are commonly used to cure skin problems, out of these 40% herbs, 32% shrubs, 25% are trees and 3 % climbers. In most of cases aerial parts of plants were used. Some of these plants are well tested on scientific basis but others are less known in scientific world. This study will provide a complete documentation of traditional knowledge to researchers for skin diseases treatment. The hidden aspects of these formulations can be tested scientifically in future.
Keywords: Herbal plants; Medicines; Skin diseases; Traditional knowledge